OXYGEN CONSUMPTION IN THE MARINE PORTUNID CRAB, OZIUS RUGULOSUS EXPOSED TO ORGANOPHOSPHATE (NUV AN) AND ORGANOCHLORIDE (DDT) PESTICIDES - Sarojini, R; Khan, A K; Nagabhushanam, R (Indian Journal of Fisheries, 2011)
Organophosphate (Nuvan) decreased the respiration of the crab, Ozius rugulosus over the controls afterexposure to 4.169, 3.388, 1.862 and 1.122 ppm for 24, 48,72 and 96 hours respectively. However, chronictreatment to 0.338 ppm increased the oxygen consumption upto 21 days and by 30th day it carne to normalÂ·levels. 0.048 ppm of DDT brought about elevation in the oxygen consumption in 24 hrs. Later exposures to0.030, 0.015 and 0.007 ppm for 48, 72 and 96 hours decreased the oxygen consumption. Chronic exposureto 0.003 ppm of DDT brought about similar results as that of Nuvan.